Oral and nasal vaccination: current prospects, challenges, and impact of nanotechnology-based delivery systems (Brazilian Journal of Pharmaceutical Sciences, 2023)
Currently, mucosal vaccine administration has stood out as an easier and non-invasive application method. It can also be used to induce local and systemic immune responses. In the COVID-19 pandemic context, nasal and oral vaccines have been developed based on different technological platforms. This review addressed relevant aspects of mucosal vaccine administration, with emphasis on oral and nasal vaccinations, in addition to the importance of using nanotechnology-based delivery systems to enable these strategies.